Assessment of arm-leg coordination in simultaneous strokes - Chollet, D. (First international symposium sciences and practices in swimming, 2006)
This work has been realised in collaboration to many persons, and more particularly Ludovic SEIFERT, Hugues LEBLANC, Laurent BOULESTEIX, Melwyn CARTER from CETAPS Laboratory. Performance in simultaneous strokes was in partly due to the capacity of swimmers to coordinate their motor actions. The assessment of arm-leg coordination, both in breaststroke than in butterfly stroke, consists to analyse the spatial-temporal relationships between the key points defining the Start and the end of the arm and the leg stroke phases. For example, in breaststroke, propulsion phases of the arms and of the legs are positives (effectives), whereas recovery phases are negatives (resistives for forward displacement). Therefore, motor Organisation in breaststroke is to superpose the negatives phases and to separate propulsion and glide phases. Coordination changes are function of skill level, gender, velocity and need some explanations.